PENGARUH BISNIS E-COMMERCE DAN SISTEM INFORMASI AKUNTANSI BERBASIS TEKNOLOGI TERHADAP KEBUTUHAN JASA AUDIT E-COMMERCE - I Made Angga Anugrah; Ida Bagus Teddy Prianthara (Universitas Pendidikan Nasional, 2018)
The Influence of E-commerce Business and Technology-based Accounting Information System on Demand of E-commerce Audit Service.This research is motivated by technological advances in the world, especially in Indonesia, which is very rapid. It is the business sector that feels the impact of technological progress and free trade. Competitive advantage, service and competitiveness are the most frequently talked about by business people today. Internet-based Information Systems are very widely used today, both in business activities and financial recording activities. The internet is a medium that is considered very simple in its operation, on the internet we can search for all information in the entire world, both about business, the state of the world economy, and conducting business activities. E-commerce audit services are services provided by auditors for e-commerce. Overseas has become a common thing for an auditor to provide e-commerce audit services. Examples of countries that have used e-commerce audit services are developed countries such as the United States, Japan and the United Kingdom. Whereas in Indonesia, e-commerce audit services are not yet well known and utilized. This study aims to find out why in Indonesia e-commerce audut services are still lacking, as we know the number of e-commerce business people in Indonesia, it is necessary to know in advance how much of the impact of the development of e-commerce businesses and the development of technology-based accounting information systems to the needs of e-commerce audit services.Keywords: Audit, E-commerce, Technology, Business, Information System